2019
DOI: 10.3390/jmse7120446
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Boulder Deposits of the Neogene World: A Synopsis

Abstract: Modern geoscience research pays significant attention to Quaternary coastal boulder deposits, although the evidence from the earlier geologic periods can be of great importance. The undertaken compilation of the literature permits to indicate 21 articles devoted to such deposits of Neogene age. These are chiefly case studies. Such an insufficiency of investigations may be linked to poor preservation potential of coastal boulder deposits and methodological difficulties. Equal attention has been paid by geoscien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Differentiated from cobbles, the base definition for a boulder adapted in this exercise is that of Wentworth (1922) for an erosional clast equal or greater than 256 mm in diameter [13]. No upper limit for this category is defined in the geological literature [14]. Triangular plots were employed to show variations in clast shape, following the design of Sneed and Folk (1958) for river pebbles [15].…”
Section: Data Collectionmentioning
confidence: 99%
“…Differentiated from cobbles, the base definition for a boulder adapted in this exercise is that of Wentworth (1922) for an erosional clast equal or greater than 256 mm in diameter [13]. No upper limit for this category is defined in the geological literature [14]. Triangular plots were employed to show variations in clast shape, following the design of Sneed and Folk (1958) for river pebbles [15].…”
Section: Data Collectionmentioning
confidence: 99%
“…Previous reviews of rocky shores [14] and megaclasts [3] confirm such research is promising. Undoubtedly, coastal megaclast deposits of Quaternary age are of special importance because the evidence of such deposits from the earlier geological periods remains scarce [3,15].…”
Section: Introductionmentioning
confidence: 99%
“…These Atlanticisland studies conform to the same procedures entailed in the analysis of boulder shapes as shown for the CBDs from Mexico's Gulf of California, and each pays attention to the key factor of rock density. Generally smaller in size, the cobbles and boulders at Støypet on Leka Island were eroded from low-grade chromite ore with a density of 3.32 g/cm 3 .This reflects the highest-density rock type yet studied for its hydrological properties in a coastal setting. The basalt from the Canary and Azores registers between 2.8 and 3.0 g/cm 3 .…”
mentioning
confidence: 97%
“…Generally smaller in size, the cobbles and boulders at Støypet on Leka Island were eroded from low-grade chromite ore with a density of 3.32 g/cm 3 .This reflects the highest-density rock type yet studied for its hydrological properties in a coastal setting. The basalt from the Canary and Azores registers between 2.8 and 3.0 g/cm 3 . The density of granodiorite from Isla San Diego in the Gulf of California was found to be 2.5 g/cm 3 [6], whereas andesite samples from Puerto Escondido and Isla San Luis Gonzaga were found to register a density of 2.3 g/cm 3 or higher [4,5].…”
mentioning
confidence: 97%
See 1 more Smart Citation